Treatment of sporadic port‐wine stains: a retrospective review of 17 cases consecutively treated by pulsed sequential dual wavelength 595 and 1064 nm laser. (10th October 2016) - Perruchoud, D.L.; Cazzaniga, S.; Heidemeyer, K.; Weber, B.; Dietrich, N.; Borradori, L.; Adatto, M.A.
Abstract: Background: Port‐wine stains (PWS) are relatively common and often cause cosmetic and psychological concerns. The pulsed dye laser is currently the treatment of choice for PWS. Objective: To assess the effectiveness of the pulsed sequential dual wavelength 595 and 1064 nm laser as first‐line treatment for PWS and to identify prognostic factors for treatment outcome in a retrospective series of 17 consecutive previously untreated patients. Methods: The response to treatment was evaluated 2 months after treatment utilizing comparative photographs and a standard physician global assessment (PGA) grading system. Furthermore, measurement of the normalized erythema index (NEI) reduction (ΔNEI%) was carried out using an image analysis system. The subjective improvement was assessed using a patient's satisfaction questionnaire. Multiple linear regression models were finally used to identify factors associated with ΔNEI% and patients' satisfaction. Results: Seventeen patients, with PWS, including 12 children were included. The average PGA assessment was 2.5 ± 1.3 corresponding to an amelioration of 50% with a high intraclass correlation coefficient among the experts. The before–after NEI showed a statistically significant mean reduction of 3.5 ± 2.6 units, corresponding to a relative reduction of 31%. Questionnaires showed that the satisfaction was very good with an average score of 6.1 points on a scale ranging from −10 to 10 points. Multiple regression analysis revealed that location in the frontotemporal area was associated with a significant reduction in ΔNEI% (38.4%; 95% CI 4.3, 72.6). Presence of PWS on the neck was associated with a lower patient satisfaction (−3.7 points; 95% CI −6.5, −0.9). There were no significant side‐effects, except for transient discomfort and purpura. Conclusions: Based on the results obtained in the largest reported series so far, the pulsed sequential dual wavelength 595 and 1064 nm laser represents an effective and safe first‐line therapeutic option for the treatment of PWS.